PENGAMBILAN KEPUTUSAN UNTUK PEMILIHAN SUPPLIER BAHAN BAKU DENGAN PENDEKATAN ANALYTIC HIERARCHY PROCESSDI PR PAHALA SIDOARJO - Miftakhul Jannah; Muhammad Fakhry; Rakhmawati Rakhmawati (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
Choosing right raw material supplier(s) is essential to reassure raw material of good quality. There are several approcahes being used for supplier selection, including method of selection and evaluation system, and models. This study aimed at evaluating and developing raw material supplier selection method in PR Pahala, Sidoarjo, Indonesia, a cigarrette company. The model used in this study was QCDFR (Quality, Cost, Delivery, Flexibility, Responsiveness) model. Several stages employed during development of the model were: establishing criterion, performance indicator of supplier of each criterion, alternative, criterion weight, performance indicator of supplier alternative and, making of spread sheet and reporting of evaluation election of supplier. There are several main suppliers of dried tobacco to be evaluated in this study, which come from four different areas, namely Madura, Bondowoso, Tulungagung, and Malang. The model developed should be able to assisst the company in the supplier selection to achieve supplier of the best performance.The most important criterion factor of supplier selection in PR Pahala is criterion of quality which had highest weight of 0,373, followed by cost of 0,266, criterion of responsivenessof 0,156, criterion of delivery of 0,128, criterion of flexibility of 0,077. Moreover, weight of selection alternative according to area were Madura with 0,311, Tulungagung 0,234, Bondowoso 0,253, Malang 0,202.